Tanggung Jawab Notaris dalam Pengamanan Data Pribadi dalam Perjanjian Notariil Pada Era Digital - Mislaini, Mislaini; Adjie, Habib (UNES Law Review, 2023)
The development of the current digital era has brought many changes, not only in the world of education and government, but in the role of Notaries as well. As a result of this change, notaries have new responsibilities in safeguarding the personal data of parties to notarial agreements. The research method used is normative research, where the author conducted a review of positive law in Indonesia, especially the regulations of Law Number 27 of 2022 concerning Personal Data Protection. Research findings indicate that Notaries act as guarantors of clients' trust and confidentiality with respect to personal information and bear responsibility for the safe and lawful handling of such information. Notaries are generally known as data controllers who have the obligation to maintain the confidentiality of personal information under their supervision. Notaries are obliged to provide warnings to the public and related agencies if there is a violation of the protection of personal identity information (PII) in their jurisdiction.